A severe urinary tract infection in an 11-year-old girl with a neurogenic bladder - Sołtysiak, Jolanta; Ostalska-Nowicka, Danuta; Frąckowiak, Karolina; Maćkowiak-Lewandowicz, Katarzyna; Patelska-Banaszewska, Magdalena; Zachwieja, Jacek (Pediatria Polska - Polish Journal of Paediatrics, 2023)
This paper presents a case of urosepsis caused by Escherichia coli in an 11-year-old girl with a neurogenic bladder. The patient had not previously been supervised by a nephrologist or urologist. On admission, significantly elevated serum markers of inflammation (C-reactive protein 32.4 mg/dl, procalcitonin 64.2 ng/ml), kidney failure (creatinine 6.9 mg/dl, pH 7.22, HCO3 6.3 mmol/l), and increased serum urea (399 mg/dl) were detected. Antibiotic therapy with rehydration was started and improved renal function without dialysis. However, a 9-cm-long perirenal abscess site was diagnosed. It required surgical treatment, which was complicated by an anaphylactic reaction to latex. Colitis caused by Clostridium difficile was also diagnosed. Hospital treatment lasted 38 days. After 4 months the patient’s glomerular filtration rate was 66 ml/min/1.73 m2 and indicated stage 2 chronic kidney disease. Because early diagnosis of urinary tract infection is crucial for preventing complications in children with neurogenic bladder, they should undergo regular nephro-urological care.